RANCANG BANGUN SISTEM PENJUALAN DAN PEMESANAN PADA APOTEK ALFARIZI BERBASIS WEB - Fadilah, Fathur Andre; Putra Laksana, Ryan (Politeknik Caltex Riau, 2025)
Apotek Alfarizi serves more than 10,000 customers annually but continues to face operational challenges due to fully manual processes in inventory management and transaction recording, resulting in data inconsistencies, delayed transaction tracking, and reduced service efficiency. This study introduces a novel fully integrated web based system that combines online sales, real time inventory management, and digital prescription verification into a single platform, which has not been previously implemented in small–medium pharmacy operations. The system was developed using the Extreme Programming (XP) methodology, featuring product management, online transactions, prescription uploads, order processing, and real time stock monitoring. System performance was evaluated using the System Usability Scale (SUS) and an operational efficiency assessment. Results show that the system reduces stock checking time by 63% and decreases stock recording errors by 42% compared to manual procedures, while achieving a SUS score of 79.71, categorized as Good and well accepted by users. The system enhances stock accuracy, accelerates transaction processing, and supports data driven decision making. Overall, the proposed platform significantly improves operational productivity and strengthens the pharmacy’s competitiveness in the digital era.